Antiviral Activity of Gold/Copper Sulfide Core/Shell Nanoparticles against Human Norovirus Virus-Like Particles - Broglie, Jessica Jenkins; Alston, Brittny; Yang, Chang; Ma, Lun; Adcock, Audrey F.; Chen, Wei; Yang, Liju (PLOS ONE, 2015)
Human norovirus is a leading cause of acute gastroenteritis worldwide in a plethora of residential and commercial settings, including restaurants, schools, and hospitals. Methods for easily detecting the virus and for treating and preventing infection are critical to stopping norovirus outbreaks, and inactivation via nanoparticles (NPs) is a more universal and attractive alternative to other physical and chemical approaches. Using norovirus GI.1 (Norwalk) virus-like particles (VLPs) as a model viral system, this study characterized the antiviral activity of Au/CuS core/shell nanoparticles (NPs) against GI.1 VLPs for the rapid inactivation of HuNoV. Inactivation of VLPs (GI.1) by Au/CuS NPs evaluated using an absorbance-based ELISA indicated that treatment with 0.083 μM NPs for 10 min inactivated 50% VLPs in a 0.37 μg/ml VLP solution and 0.83 μM NPs for 10 min completely inactivated the VLPs. Increasing nanoparticle concentration and/or VLP-NP contact time significantly increased the virucidal efficacy of Au/CuS NPs. Changes to the VLP particle morphology, size, and capsid protein were characterized using dynamic light scattering, transmission electron microscopy, and Western blot analysis. The strategy reported here provides the first reported proof-of-concept Au/CuS NPs-based virucide for rapidly inactivating human norovirus.